2021
DOI: 10.14716/ijtech.v12i1.4115
|View full text |Cite
|
Sign up to set email alerts
|

Modular Isolation Units for Patients with Mild-to-Moderate Conditions in Response to Hospital Surges Resulting from the COVID-19 Pandemic

Abstract: This paper presents a design proposal of an Isolation Recovery House (IRH), an adaptable modular isolation care unit specifically designed for patients with mild-to-moderate conditions as a response to an infectious disease outbreak. In particular, the study responds to the current COVID-19 pandemic, which urges the installation of isolation facilities as quickly as possible. The study offers a design solution that could expand the capacity for isolation facilities, especially in underdeveloped or developing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In particular, this study attempts to analyze the role of the two operations types, the tours and the maps, within a sequence of a wayfinding journey in a hospital building. Some studies in hospital and healthcare facilities have revealed the role of spatial configuration in hospital performance (Johanes & Atmodiwirjo, 2015;Sengke et al, 2020;Yatmo et al, 2018Yatmo et al, , 2021, including issues with wayfinding (Pati et al, 2015;Carpman et al, 2016;Johanes & Yatmo, 2018). This current study demonstrates how the movement of visitors can take place in a particular spatial configuration of a hospital.…”
Section: Introductionmentioning
confidence: 51%
“…In particular, this study attempts to analyze the role of the two operations types, the tours and the maps, within a sequence of a wayfinding journey in a hospital building. Some studies in hospital and healthcare facilities have revealed the role of spatial configuration in hospital performance (Johanes & Atmodiwirjo, 2015;Sengke et al, 2020;Yatmo et al, 2018Yatmo et al, , 2021, including issues with wayfinding (Pati et al, 2015;Carpman et al, 2016;Johanes & Yatmo, 2018). This current study demonstrates how the movement of visitors can take place in a particular spatial configuration of a hospital.…”
Section: Introductionmentioning
confidence: 51%
“…During the pandemic, coproduction is vital as the crisis has led to higher urgency for shared responsibility, particularly in providing resources and services for health and wellbeing needs (Steen and Brandsen, 2020;Yatmo et al, 2021). The flows of food in society have been beleaguered by multiple disturbances, such as lagging food processing and disrupted distribution networks, which have created food supply issues (Hobbs, 2020).…”
Section: Food Coproduction and Neighborhoodmentioning
confidence: 99%
“…Malaysia's Ministry of Health (MOH) has classified five different categories of COVID-19 according to the patients' symptoms (Malaysia's Ministry of Health, 2022). Every adult under the age of 60 with mild Category 1 and Category 2 illnesses, without or with stable or controlled comorbidities only, are eligible for selfquarantine at home or at special isolation units (Yatmo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%